Severe immune thrombocytopenia that developed immediately after COVID-19 in a school-aged patient: A case report - Shinno, Kazuma; Banno, Yoshinori; Kamimaki, Isamu (Frontiers in Pediatrics, 2023)
Immune thrombocytopenia (ITP) is an autoimmune disorder that is sometimes triggered by a preceding viral infection and is characterized by a transient or persistent decrease in the platelet (Plt) count. Herein, we report the first pediatric case of severe ITP that developed immediately after the diagnosis of coronavirus disease 2019 (COVID-19) in a school-aged girl. A previously healthy six-year-old girl was diagnosed with COVID-19 a day before experiencing a high fever, sore throat, and headache. She also presented with gingival hemorrhage, petechiae around both eyes and on the chest, and ecchymosis on her right leg. Based on the mucosal hemorrhage and a very low Plt count of 3×103/μL, we diagnosed her with severe ITP and urgently treated her with intravenous immunoglobulin (IVIG) to prevent life-threatening hemorrhage. The Plt count increased to 266×103/μL one week after treatment with IVIG. Given the possibility of severe ITP secondary to COVID-19, patients with COVID-19 should be carefully examined for the signs of ITP, such as mucosal hemorrhage. Their Plt counts should also be monitored.